Principles of Politics in Islam Based on the Qur'an and Their Application During the Caliphate Era: Prinsip-Prinsip Politik Dalam Islam Berdasarkan Al-Qur’an Dan Penerapan Pada Masa Kekhalifahan - Ambiya, Lulu Nurul; Nur Rohman, Ilham; Najmul Umam Assondani, Muhammad Mufti (JSPH : Jurnal Sosial Politik Humaniora, 2024)
This research examines the political principles of Islam based on the teachings of the Qur'an and their application during the reign of the Khulafaur Rashidin. Values such as justice, deliberation, equality before the law and social welfare are the main pillars of the Islamic political system. The article also reviews the implementation of politics by the four caliphs, namely Abu Bakr, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib, highlighting the successes, challenges, and policies they implemented in leading the people. This study confirms that politics in Islam is not only centred on power, but also prioritises the implementation of sharia, the creation of peace, and the improvement of people's welfare.